Lejeuneaceae (Marchantiophyta) in Curug Semirang, Central Java, Indonesia - Annisa Audita Utomo; Lilih Khotimperwati; Jumari Jumari (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.